2020
DOI: 10.3389/fnbeh.2020.00037
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Profiling in Early Adolescence and Early Adulthood of Male Wistar Rats After Short and Prolonged Maternal Separation

Abstract: Early-life stress and its possible correlations to genes, environment, and later health outcomes can only be studied retrospectively in humans. Animal models enable the exploration of such connections with prospective, well-controlled study designs. However, with the recent awareness of replicability issues in preclinical research, the reproducibility of results from animal models has been highlighted. The present study aims to reproduce the behavioral effects of maternal separation (MS) previously observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“… 8 Exposure to MS, using a protocol very similar to that in the present manuscript, associates with behavioral changes including higher anxiety-like behavior in early adolescence (P22-35) in male rats. 52 , 53 , 54 , 55 , 56 …”
Section: Discussionmentioning
confidence: 99%
“… 8 Exposure to MS, using a protocol very similar to that in the present manuscript, associates with behavioral changes including higher anxiety-like behavior in early adolescence (P22-35) in male rats. 52 , 53 , 54 , 55 , 56 …”
Section: Discussionmentioning
confidence: 99%
“…In rodents and non-human primates, numerous studies have demonstrated that ELA results in behavioral phenotypes that suggest underlying dysfunction in reward-related brain regions (Molet et al, 2014 ; Andersen, 2015 , 2018 ; Wakeford et al, 2018 ; Bonapersona et al, 2019 ; Birnie et al, 2020 ). The particular behavioral outcomes of ELA in animal models can vary depending on the type, timing, and duration of the paradigm, the species and strain of animal, and the timing and type of behavioral assays (Schmidt M. V. et al, 2011 ; Molet et al, 2014 ; Andersen, 2015 ; Walker et al, 2017 ; Brenhouse and Bath, 2019 ; Demaestri et al, 2020 ; Lundberg et al, 2020 ), as well as sex (Kundakovic et al, 2013 ; Bath, 2020 ). While this poses a challenge for interpreting this vast literature, the variability also mirrors human experience; indeed, ELA in humans can take many different forms, such as poverty, trauma, physical or sexual abuse, and neglect, and these, in combination with other environmental and biological factors, likely contribute to individual differences in clinical outcomes (Shand et al, 2011 ; Daskalakis et al, 2013 ; Sheridan and McLaughlin, 2014 ; Strathearn et al, 2020 ), highlighting the sensitivity of the brain to different types of stressors during these developmental periods.…”
Section: How Does Ela Provoke Anhedonia Oud and Comorbidities? A Nementioning
confidence: 99%
“…Several studies have shown that maternal separation changes the offspring’s neuroendocrine and behavioral stress response in an opposite direction to neonatal handling; maternally separated animals show increased anxiety-like behavior, depressive behavior and impaired cognitive functions ( Banqueri et al, 2017 , Daniels et al, 2004 , de Souza et al, 2022 , Huot et al, 2001 , Lee et al, 2007 , Tsotsokou et al, 2021 ). Other studies report no significant differences on the HPA axis, on adult anxiety-like behavior, and cognition between maternally separated and control animals ( Biagini et al, 1998 , Hulshof et al, 2011 , Lehmann et al, 1999 , Lehmann et al, 1998 , Lundberg et al, 2020 , Shalev and Kafkafi, 2002 ).…”
Section: Introductionmentioning
confidence: 90%